The Relationship Between Mother-Child Interaction and Spiritual Well-being and Child Behavioral Disorders Through the Moderating Role of Mental Health in Mothers of Children With Hearing Impairment - Parviz Asgari; Parvin Ehteshamzadeh; Maryam Pourseyyed Mohammad; Farah Naderi (Gonabad University of Medical Sciences, 2021)
Background: Mother-child interaction and spiritual well-being can influence child behavioral disorders by affecting the mother's mental health. The present study was done to investigate the relationship between mother-child interaction and spiritual well-being and child behavioral disorders with the mediation of mental health in mothers of children with hearing impairment. Methods: The descriptive correlational study used a path analysis. The statistical population included 1580 mothers of children with hearing impairment in Tehran in 2019. The sample size was determined using Morgan's sample size table. The samples were selected based on stratified random sampling. To collect the required data, 310 questionnaires based on the research variables were provided to the participants and a total of 284 questionnaires were analyzed following the elimination of incomplete questionnaires. The research instruments included the Behavior Disorders Questionnaire, the Child-Parent Interaction Questionnaire, the Spiritual Well-being Questionnaire, and the Mental Health Questionnaire. The proposed model was evaluated using path analysis by AMOS v. 24 software. Results: The results showed that there was a significant relationship between spiritual well-being and child behavioral disorders (P<0.01), mental health and child behavioral disorders (P<0.01), child-mother interaction and mental health (P<0.01), and spiritual well-being and mental health (P<0.01), but there was no a significant relationship between child-mother interaction and child behavioral disorders (P>0.05). Moreover, indirect paths of child-mother interaction and child behavioral disorders with a mediating role of mental health (P<0.01) and spiritual well-being and child behavioral disorders with a mediating role of mental health were significant (P<0.05). Conclusion: According to the results of this study, the proposed model had a good fit, and is an important step in identifying the factors affecting the child behavioral disorders of children with hearing impairment.